2018
DOI: 10.1038/s41598-018-30661-w
|View full text |Cite
|
Sign up to set email alerts
|

A manganese porphyrin-based T1 contrast agent for cellular MR imaging of human embryonic stem cells

Abstract: MRI for non-invasive cell tracking is recognized for enabling pre-clinical research on stem cell therapy. Yet, adoption of cellular imaging in stem cell research has been restricted to sites with experience in MR contrast agent synthesis and to small animal models that do not require scaled-up synthesis. In this study, we demonstrate the use of a gadolinium-free T1 contrast agent for tracking human embryonic stem cells. The agent, MnPNH2, is an easily synthesized manganese porphyrin that can be scaled for larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
1
17
0
3
Order By: Relevance
“…To avoid this interference, an alternative bright-contrast cell tracking process using paramagnetic T1 contrast agents was applied in preclinical settings. Examples of T1 contrast agents identified as Gd-DTPA (Magnevist, FDA approved) and gadodiamide (Omniscan, FDA approved), as well as manganese porphyrin-based contrast agents, such as MnAMP, MnPNH 2 , and MnEtP, were applied in preclinical settings [ 104 , 110 112 ]. Amongst T1 cell-labeling agents, there have been a plethora of approaches based on both gadolinium (Gd) and manganese.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid this interference, an alternative bright-contrast cell tracking process using paramagnetic T1 contrast agents was applied in preclinical settings. Examples of T1 contrast agents identified as Gd-DTPA (Magnevist, FDA approved) and gadodiamide (Omniscan, FDA approved), as well as manganese porphyrin-based contrast agents, such as MnAMP, MnPNH 2 , and MnEtP, were applied in preclinical settings [ 104 , 110 112 ]. Amongst T1 cell-labeling agents, there have been a plethora of approaches based on both gadolinium (Gd) and manganese.…”
Section: Resultsmentioning
confidence: 99%
“…An in vitro experiment of the DDNP-SPIONs binding to β-amyloid aggregates showed that the combination (DDNP-SPIONs) induced the fluorescence enhancement of the DDNP-SPIONs. The research by Venter et al, 2018 [9], on gadolinium free Mn porphyrin amine as a MRI contrast agent for T1-based cellular imaging and tracking of human embryonic has shown great potential of porphyrins as contrast agents as their study reported on the oncological capabilities of chelated porphyrins.…”
Section: Porphyrins In Medicinal Imagingmentioning
confidence: 99%
“…Progressive research on porphyrins within these fields has resulted in great scientific and industrial interest in porphyrins, metalloporphyrins, and their related compounds. The bio-application of porphyrins has thus expanded into bio-sensors, fluorescence tracking, in vivo MRI, and PET/CT imaging to photo-immuno-therapy [8,9]. Porphyrins have shown great potential within the medical imaging field (or techniques that create visual representation of the interior of the body for clinical and medical intervention) due to their pharmacological properties such as low toxicity, high tumor uptake, and the possibility of forming complexes with metals.…”
Section: Introductionmentioning
confidence: 99%
“…This exogenous labeling approach, however, works well only for short-term studies and cannot attain the desired capability for monitoring over the long term. Multiple factors underlie this shortcoming, foremost of which are label dilution upon cell division, leakage of contrast agent from cells ( Venter et al., 2018 ), and non-specific labeling of macrophages that take up contrast agents released from dying cells ( Ma et al., 2015 ). Longitudinal cell tracking requires a method that provides sustained contrast specific to the viable cells of interest.…”
Section: Introductionmentioning
confidence: 99%